A Critical Review on the Relevance of Paracetamol for Procedural Pain Management in Neonates - Allegaert, Karel (Frontiers in Pediatrics, 2020)
Effective and safe pain relief in neonates matters. This is not only because of ethical constraints or human empathy, but even more because pain treatment is an important and crucial part of contemporary medical, paramedical and nursing care to improve outcome in neonatal intensive care graduates. Paracetamol (acetaminophen) is likely one of the pharmacological tools to attain this, with data on prescription practices suggesting that paracetamol is somehow the ‘rising star’ in neonatal pain management. Besides very rare, topical clinical scenarios like peripartal asphyxia and subsequent whole body hypothermia or cardiorespiratory support devices, data on paracetamol pharmacokinetics and metabolism were reported throughout neonatal age or weight ranges, and we have summarized these data. In this review, we subsequently aimed to provide the reader with the currently available observations on the use of paracetamol as analgesic for different pain syndromes (major surgery, minor surgery or trauma, procedural pain), with focus on the limitations of paracetamol when prescribed for neonatal procedural pain management. We hereby intentional will not discuss other indications (patent ductus arteriosus, fever) for paracetamol administration in neonates. Based on the available evidence, paracetamol has opioid sparing effects for major pain syndromes, is effective to treat minor to moderate pain syndromes, but fails for effective procedural pain management in neonates. This efficacy failure for procedural pain management should stimulate us to continue to search for more effective interventions, including non-pharmacological interventions and preventive strategies. Furthermore, there are also upcoming association-type of epidemiological studies on the relation between exposure to analgesics - including paracetamol - and negative short- or long-term outcome characteristics (neuro-behavioral, atopy and fertility). Consequently and in addition to search for effective alternatives to prevent or treat pain, studies on long-term outcome following paracetamol exposure are needed to inform all stakeholders on the full effect-side effect balance of the different strategies to treat pain.